Dowling-Degos disease with hidradenitis suppurativa and inflammatory arthritis in two generations - Anju George; Renu George; Ashish J Mathew; Ramesh B Telugu (Wolters Kluwer Medknow Publications, 2020)
Dowling-Degos disease (DDD) is a rare autosomal dominant genodermatosis characterized by reticulate brown-to-black pigmentation of the flexures, pitted perioral acneiform scars, and comedo-like follicular papules on the flexures. The diagnosis is based on characteristic clinical and histopathological features. DDD has been found to occur in association with hidradenitis suppurativa (HS), arthritis, epidermoid cysts, keratoacanthomas, and squamous cell carcinoma. To date, there is only one report of DDD associated with HS and polyarticular arthritis.